2005
DOI: 10.1074/jbc.m411596200
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 7 Inhibits Prolactin, Growth Hormone, and Leptin Signaling by Interacting with STAT5 or STAT3 and Attenuating Their Nuclear Translocation

Abstract: We report here the role of one of the less studied members of the family of suppressors of cytokine signaling (SOCS), namely SOCS-7, in cytokine signaling. We demonstrate that SOCS-7 inhibits prolactin (PRL), growth hormone (GH), or leptin (LEP) signaling mediated through STAT3 and STAT5 in a dose-dependent manner. SOCS-7 also attenuated STAT3 and STAT5 signaling induced by overexpression of JH1, the catalytic subdomain of JAK2. Since SOCS-7 interacted with phosphorylated STAT3 or STAT5, we assumed that SOCS-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 29 publications
4
51
0
2
Order By: Relevance
“…SOCS3 induced by leptin binds to the leptin receptor-associated kinase JAK2 in a leptin-dependent manner in vitro, antagonizes kinase activity, and thereby attenuates proximal leptin signaling through the JAK-STAT pathway (17). Intriguingly, another SOCS protein, SOCS7, has recently been shown to act as an inhibitor of leptin-activated STAT3 and STAT5 signaling by abolishing their translocation to the nucleus (35). We found that SOCS molecules may also represent candidate mediators of leptin-dependent inhibition of insulin promoter activity in pancreatic ␤-cells.…”
Section: Discussionmentioning
confidence: 75%
“…SOCS3 induced by leptin binds to the leptin receptor-associated kinase JAK2 in a leptin-dependent manner in vitro, antagonizes kinase activity, and thereby attenuates proximal leptin signaling through the JAK-STAT pathway (17). Intriguingly, another SOCS protein, SOCS7, has recently been shown to act as an inhibitor of leptin-activated STAT3 and STAT5 signaling by abolishing their translocation to the nucleus (35). We found that SOCS molecules may also represent candidate mediators of leptin-dependent inhibition of insulin promoter activity in pancreatic ␤-cells.…”
Section: Discussionmentioning
confidence: 75%
“…Direct target specificity for GHR appears to be restricted to the SH2 domains of SOCS3, which binds pY333 and pY338, and SOCS2 and CIS1, which target the membrane-distal pY487 and pY595 sites (1). SOCS2 is uniquely identified as a primary GHR inhibitor in vivo by its overgrowth knockout phenotype in mice (5); other SOCS family knockout mice show no overgrowth phenotype or are growth-retarded (25)(26)(27). The binding affinity of SOCS2 for the primary pY595 site is typical for physiological SH2-ligand interactions determined by isothermal titration calorimetry (ITC) and 5-fold higher than for the erythropoietin receptor (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SOCS1 can inhibit JAK2 through either its N-terminal kinase inhibitory region or SH2 domains and also mediate its degradation by means of the SOCS box (17). Downstream inhibition of STAT3 and STAT5 may also be effected by SOCS7 to suppress multiple cytokine pathways (25). Direct target specificity for GHR appears to be restricted to the SH2 domains of SOCS3, which binds pY333 and pY338, and SOCS2 and CIS1, which target the membrane-distal pY487 and pY595 sites (1).…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulation of STAT5 is known to be mediated by tyrosine phosphatases and suppressors of cytokine signaling (SOCS) (Aoki and Matsuda, 2000;Aoki and Matsuda, 2002;Chen et al, 2004;Cornish et al, 2003;Hoyt et al, 2007;Martens et al, 2005). Another possible means of negative regulation is STAT5 export from the nucleus.…”
Section: Stat5a Nuclear Trafficking 3339mentioning
confidence: 99%